The Problems of Teaching Speaking with Respect to the Teaching Methodology: Task-Based Language Teaching - Musliadi Musliadi (Universitas Cokroaminoto Palopo, 2016)
The study deals with the problems of teaching and learning speaking, in particular those which are most relevant in the context of developing oral skills at the advanced level of foreign language proficiency. The complex nature of spoken language must be taken into account and reflected at each stage of the learning process. Thus, the study examines the difficulties connected with choosing the appropriate learning and teaching approach and discusses the relations of the learning approach into how it affects the teaching of speaking in the classroom. It also suggests some speaking activities which seem most suitable for advanced language learners in the light of the above learning approach proposed.